2016
DOI: 10.1007/s10488-016-0779-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Race, Patient Activation, and Working Alliance: Implications for Patient Engagement in Mental Health Care

Abstract: This study explored the relationship between race and two key aspects of patient engagementpatient activation and working alliance -among a sample of African-American and White veterans (N=152) seeking medication management for mental health conditions. After adjusting for demographics, race was significantly associated with patient activation, working alliance, and medication adherence scores. Patient activation was also associated with working alliance. These results provide support for the consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…American veterans experiencing mental health issues. 17 The requirement to better understand BAME perspectives is supported by another qualitative study into the impact of stigma on helpseeking behaviour in mental health. The complexity of spiritual beliefs, stigma and the need for improved co-produced work on service improvement was stressed.…”
Section: Anmentioning
confidence: 99%
See 1 more Smart Citation
“…American veterans experiencing mental health issues. 17 The requirement to better understand BAME perspectives is supported by another qualitative study into the impact of stigma on helpseeking behaviour in mental health. The complexity of spiritual beliefs, stigma and the need for improved co-produced work on service improvement was stressed.…”
Section: Anmentioning
confidence: 99%
“…This was a small, qualitative study, focusing on one medical centre and therefore not intended to be generalizable to a wider population. However, it highlights the poorly explored perspectives of African American veterans experiencing mental health issues 17. The requirement to better understand BAME perspectives is supported by another qualitative study into the impact of stigma on help‐seeking behaviour in mental health.…”
Section: Background and Rationalementioning
confidence: 99%
“…Of the 10 studies, six used correlational cross-sectional designs (Chen et al, 2014;Eliacin et al, 2018;Ivey et al, 2018;Kukla et al, 2013;Pinto et al, 2017;Sacks et al, 2014), one used a correlational longitudinal design (Allen et al, 2017), two were secondary analyses from randomized controlled trials that reported baseline associations between activation and other factors (Oles et al, 2015;Singla et al, 2020), and one was a randomized pragmatic clinical trial (Mccusker et al, 2016). Most of the participants in the studies were recruited from primary care clinics, mental health centres and communities.…”
Section: Associations Between Levels Of Patient Activation and Other Factorsmentioning
confidence: 99%
“…Studies examined associations between activation and education, gender, age, employment status or insurance but found none (Allen et al, 2017;Chen et al, 2014;Kukla et al, 2013;Mccusker et al, 2016;Oles et al, 2015). Only two of the five studies that examined associations between race/ethnicity (Allen et al, 2017;Chen et al, 2014;Eliacin et al, 2018;Kukla et al, 2013;Oles et al, 2015) found associations, and both these studies found that White persons had higher levels of activation that Black persons (Chen et al, 2014;Eliacin et al, 2018). One study found associations between activation and residence in several U.S. Census Divisions (i.e.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Often patients and family members will not address bias directly, but may offer clues in the form of frustration, disengagement, and questions about how testing and treatment decisions are made (13). These clues often generate discomfort in clinicians and staff, and defensiveness is a natural reaction, but an alternative is to see these reactions as an invitation to engage immediately, honestly, and compassionately. A sk: “You mentioned celebrities who have had testing and I noticed everyone you mentioned is white.…”
Section: Respond To Cues and Acknowledge Reality Artfullymentioning
confidence: 99%